2009
DOI: 10.1007/s10750-009-9831-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bacterioplankton communities in three mariculture ponds farming different commercial animals in subtropical Chinese coast

Abstract: In order to explore the responses of the bacterioplankton community to different types of aquaculture environments, three mariculture ponds comprised of groupers (Epinephelus diacanthus, ED), prawns (Penaeus vannamei, PV), and abalone (Haliotis diversicolor supertexta, HDS) in southeast, coastal China were investigated. The free-living bacterial diversity was analyzed through the construction of 16S rDNA clone library. A total of 203 16S rDNA sequences from three clone libraries were classified into 118 operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This apparent reduction in bacterial diversity due to aquaculture should be confirmed in other systems because it might not be a general finding. For example, Wei et al (2009) observed high bacterial diversity in fish ponds dedicated to the culture of two different species (grouper, Epinephelus diacanthus ; and abalone, Haliotis diversicolor supertexta ), and they related this to the composition of the feeding supplied. However, it should be taken into account that fish pens and ponds are completely different aquaculture systems and therefore the effect on microbial communities might also be different.…”
Section: Microbial Communities In Nutrient‐enriched Environmentsmentioning
confidence: 99%
“…This apparent reduction in bacterial diversity due to aquaculture should be confirmed in other systems because it might not be a general finding. For example, Wei et al (2009) observed high bacterial diversity in fish ponds dedicated to the culture of two different species (grouper, Epinephelus diacanthus ; and abalone, Haliotis diversicolor supertexta ), and they related this to the composition of the feeding supplied. However, it should be taken into account that fish pens and ponds are completely different aquaculture systems and therefore the effect on microbial communities might also be different.…”
Section: Microbial Communities In Nutrient‐enriched Environmentsmentioning
confidence: 99%
“…Previous studies have indicated that mariculture systems, including intensive fish and shrimp farms, integrated mangrove forest aquaculture systems and cage farms, are responsible for the discharge of significant quantities of effluent into the surrounding mangrove ecosystems (Troell et al, 1999;Fitzgerald, 2002;Wei et al, 2009;De Silva, 2012), due to the fact that nutrient enrichment and the presence of residual waste from the effluent alter bacterial communities (Zhang et al, 2009;Ghosh et al, 2010). However, fewer researchers investigated the bacterial community of seawater in mangroves affected by the mariculture.…”
Section: Discussionmentioning
confidence: 99%
“…Apprill et al 2016), shows similar community changes in response to environmental aquaculture pollution (Sousa et al 2006, Garren et al 2008, Fodelianakis et al 2014, Xiong et al 2015. For example, in aquaculture environments such as a coastal shrimp pond in southeast China (Wei et al 2009) and a fish farm north of Crete, Greece (Fo -delianakis et al 2014), the seawater microbial communities had reduced phylogenetic diversity and experienced overall shifts in community composition. Increases in Proteobacteria, free-living bacteria, and virus-like particles were also noted in the oligotrophic reef waters of the Philippines, correlating with organic nutrient enrichment caused by a fish farm (Garren et al 2008).…”
Section: Introductionmentioning
confidence: 97%